2022
DOI: 10.1186/s12978-022-01473-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of preconception risk factors for adverse pregnancy outcome among women from tribal and non-tribal blocks in Nashik district, India: a cross-sectional study

Abstract: Background Although critical, the preconception phase in women’s lives is comparatively ignored. The presence of some risk factors during this phase adversely affects the wellbeing of the woman and the pregnancy outcome. The study objectives were to measure the prevalence of various known risk factors for adverse pregnancy outcome in the preconception period of women and their comparison between blocks. Methods This was a community-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…There were 13 Primary Health Centers (PHCs) in the intervention and 15 in the comparison blocks. Detailed information about the study setting has already been reported ( Doke et al, 2022 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 13 Primary Health Centers (PHCs) in the intervention and 15 in the comparison blocks. Detailed information about the study setting has already been reported ( Doke et al, 2022 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…ASHAs are women from the community and act as a bridge between government and the community. Detailed information about the participants' enrolment, baseline characteristics, and prevalence of selected risk factors was collected and published ( Doke et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…While the evidence on pregnancy during early adolescence and later adolescence is yet to be investigated. Other major preconception risk factors among adolescents are mental health, poor nutrition, violence, and non-communicable diseases, which have not been extensively studied [ 7 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%